The poems of Emily Dickinson - Dickinson, Emily, 1830-1886 (Belknap Press of Harvard University Press, 2005)
After many years of preparation by Ralph Franklin, this edition of Emily Dickinson's poems contains 1789 poems in all, the largest number ever assembled.